The risks of derivatives contracts and their reflections on the global financial crisis Analytical study in (Toronto – Dominion) bank - عبد الحكيم, هشام طلعت (Journal of Economics and Administrative Sciences, 2018)
The research tacklets the role of risks arising from the excessive use of derivative contracts for trading in financial crises, including the recent global financial crisis in (2008) which is known the mortgage crisis.   In order to prove the hypothesis of the research, the risk index of derivative contracts has been chosed as expressed in the measure of (value at risk) to be the main field for testing the hypothesis of research. The duration of the contract  has been also chased  for (15) years between the years (2001- 2015), the period preceding the global financial crisis, while the second represents the period of time that followed. The research reached a number of conclusions, but the most important one was that there was a significant difference between the risk of derivative contracts in the two periods preceding the global financial crisis and those that followed. The research recommended that the management of the (Toronto - Dominion)bank  should measure its revenues from its transactions in derivatives contracts periodically and in detail with a view to reducing and managing risk and achieving the desired objectives of investing in these contracts